2018
DOI: 10.1016/j.ymssp.2017.08.024
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting input sparsity for joint state/input moving horizon estimation

Abstract: This paper proposes a novel time domain approach for joint state/input estimation of mechanical systems. The novelty consists of exploiting compressive sensing (CS) principles in a moving horizon estimator (MHE), allowing the observation of a large number of input locations given a small set of measurements. Existing techniques are characterized by intrinsic limitations when estimating multiple input locations, due to an observability decrease. Moreover, CS does not require an input to be characterized by a sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…The real and imaginary parts of the force acting on location j are selected with L j , and the slack variables s and t j are selected with g and c j , respectively. The vectors f ∈ R 2N np+np+1 and b ∈ R 2N n d are defined as: 10) where the matrix 1 m×n ∈ R m×n contains ones.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The real and imaginary parts of the force acting on location j are selected with L j , and the slack variables s and t j are selected with g and c j , respectively. The vectors f ∈ R 2N np+np+1 and b ∈ R 2N n d are defined as: 10) where the matrix 1 m×n ∈ R m×n contains ones.…”
Section: Discussionmentioning
confidence: 99%
“…Qiao et al [9], however, proposed the use of interior point methods to solve this regularized problem. Kirchner et al [10] recently developed the compressive sensing-moving horizon estimator (CS-MHE) which combines a moving horizon estimator (MHE) with an ℓ 1 regularization term. This allows for a recursive solution of the force localization problem in the time domain.…”
Section: Introductionmentioning
confidence: 99%
“…This approach is chosen as in general no prior information on the input is assumed to be known. However, if useful information is available, e.g., periodicity of the input, other input models can be employed, as in [ 24 ].…”
Section: State-input Estimation For Mb Modelsmentioning
confidence: 99%
“…In pursuit of this goal, the objective of this paper is to implement a Gaussian process latent force model which improves upon existing methods by reducing the dependency on manual tuning of covariance matrices associated with the unknown inputs and also provides numerical stability with respect to observability of the augmented state-space formulation when used with only acceleration measurements. The location of the inputs is assumed to be known, however studies on input localization can be found in [26,27,28].…”
Section: Objectivementioning
confidence: 99%